FORMATION AND DEVELOPMENT OF TOOLS TO ENSURE DRUG SAFETY OF MODERN SOCIETY: BASED ON THE EXPERIENCE OF THE UNITED NATIONS OFFICE ON DRUGS AND CRIME AND THE EUROPEAN MONITORING CENTER FOR DRUGS AND DRUG ADDICTION - Shinkevich, Vladimir E.; Kupriyanchik, Tatiana V. (Society and security insights (Online), 2023)
The topicality of the article is due to the importance for building an anti-drug policy to counteract the spread of using narcotic drugs and psychotropic substances by the population or its individual groups for non-medical purposes both in Russia and in its individual regions and for making administartive decisions, the need to take into account the positive domestic and foreign experience of anti-drug activities. The authors note the importance of anti-drug activity as an integral component of ensuring the security of modern society; attention is drawn to the fact that drug addiction and narcotism are capable of reducing the population to a critical value in less than one generation of people, just like the most dangerous epidemics and pandemics. The results of the research are of interest to the subjects of the anti-drug policy of the region, for the development of administrative decisions to ensure its drug safety, organization and formation of anti-drug prevention based on accumulated experience.